2011
DOI: 10.1111/j.1365-2745.2011.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate cues and resources interact to determine seed production by a masting species

Abstract: Summary1. Mast seeding is the intermittent production of large quantities of seed across a perennial plant population. Such seeding events in many plant species are initiated by climatic cues, but whether these cues act solely as triggers or also via alterations to nutrient availability is unclear. 2. Here, we examine the effect of nitrogenous fertilization on the relationship between seed production in Nothofagus solandri var. cliffortioides and two climatic cues (rainfall and temperature) at specific stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
140
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(155 citation statements)
references
References 46 publications
(132 reference statements)
11
140
0
Order By: Relevance
“…Other studies found similar correlations, e.g. Richardson et al (2005) related seed production of Nothofagus solandri with temperature, finding that cold and humid summers produce a higher number of fruits, whereas Smaill et al (2011) also determined the influence of rainfall for the same species. Kon et al (2005) found correlations between 9 Regeneration, harvesting and climate minimum temperatures of the previous spring and seed production of Fagus crenata forests, as well as Masaki et al (2008).…”
Section: Relationships Between Regional Climate With Seed Production supporting
confidence: 51%
“…Other studies found similar correlations, e.g. Richardson et al (2005) related seed production of Nothofagus solandri with temperature, finding that cold and humid summers produce a higher number of fruits, whereas Smaill et al (2011) also determined the influence of rainfall for the same species. Kon et al (2005) found correlations between 9 Regeneration, harvesting and climate minimum temperatures of the previous spring and seed production of Fagus crenata forests, as well as Masaki et al (2008).…”
Section: Relationships Between Regional Climate With Seed Production supporting
confidence: 51%
“…Evidence from New Zealand beech (Nothofagus spp.) forests support these predictions (Smaill et al 2011), as warm summer temperatures are hypothesized to increase soil N mineralization, leading to greater accumulation of carbon-based resources within plants and more frequent and intense masting (Richardson et al 2005). By contrast, plants on soils with fewer mineral nutrients should take longer to accumulate the internal resources required for flowering, and hence, mast less frequently and intensely (Kelly and Sork 2002).…”
Section: Introductionmentioning
confidence: 69%
“…Species on N-poor soils may thus require more favorable growing conditions to accumulate sufficient N to invest in seeds. Increased soil N mineralization at higher spring temperatures may exceed a species-specific threshold required to initiate flowering (Richardson et al 2005, Smaill et al 2011), but will foremost depend on growing conditions; e.g., species on N-poor soils may be as likely to flower as those on N-rich soils at high summer temperatures. While we have identified an important link between flowering, temperature, and soil nutrient availability, other factors may be mutually correlated with flowering and species' abilities to exploit soils with different N supply, including genetic variation crassiuscula is represented by CRA (solid gray lines), C. pallens by PAL (solid black lines), C. rigida by RIG (dashed blue lines), C. rubra by RUB (dotted orange lines), and C. teretifolia by TER (dotted-dashed green lines).…”
Section: Role Of Soil Nutrients In Modulating Floral Inductionmentioning
confidence: 99%
“…The effect of weather on Mediterranean forests, however, may not only be of relevance for water availability. Precipitation may also increase mineralisation rates in soils (Jarvis et al 2007) and nutrient availability to plants (Sardans and Peñuelas 2007;Smaill et al 2011) in Mediterranean areas. The combined pulse of water and nutrient availability may thus produce a synergic effect boosting large seed crops in these forests.…”
Section: Short-time Resource Accumulation and Mastingmentioning
confidence: 99%